Thirty years of mass exchanger network synthesis – A systematic review. (1st July 2021) - Short, Michael; Isafiade, Adeniyi Jide
Abstract: This work provides the first systematic critical review of mass exchanger network synthesis literature. Mass exchanger networks play a central role in many pollution reduction and resource utilisation processes and contain many complex decisions to be made including exchanger types, sizing, and mass separating agent selection. We present a comprehensive review of the key milestones in the development of methods for mass exchanger network synthesis and focus on the key challenges that have hindered research in this area from flourishing in the manner of the conceptually similar heat exchanger network synthesis problem. We find that several important research questions remain for the methods to find wider use in industry. More efficient techniques for solving nonconvex mixed-integer nonlinear programs and better methods of including more accurate, higher-order unit models for industrial problems within network optimisation problems are particularly important, as current methods provide highly simplified unit representations that do not take into account many important practical design considerations that have significant cost implications. Furthermore, we identify significant potential for further research into increasing the scope of the problem to include issues such as flexibility and controllability, inter-plant mass exchanger networks, batch processes, retrofit and further integration of heat and mass exchanger networks, with research into these domains limited. Through further research of these under-developed applications of mass exchanger network synthesis, we envision that techniques for mass integration can become a powerful tool to enhance mass integration techniques for sustainable cleaner production technology. Highlights: Existing synthesis methods have been mainly graphical and deterministic. More robust methods should be developed for multicomponent systems. Most methods have included simplified unit designs rather than detailed ones. Controllability and flexibility despite being crucial have received less attention. Opportunities for interplant mass integration should be explored.